The Internet: Friend or Foe of Antibiotic Resistance? Results of a Cross-Sectional Study among Italian University Students - Francesca Licata; Silvia Angelillo; Alessandra Oliverio; Aida Bianco (MDPI AG, 2021)
The study aims were to investigate knowledge and attitudes towards antibiotics and antibiotic resistance (ABR), and to assess the extent of practices regarding antibiotic consumption and Internet use among university students in Southern Italy. Data were collected through an anonymous online questionnaire from 1 April to 14 April 2021. The eligibility criteria for the study were: (i) age between 18 and 30 years and (ii) registered as an undergraduate student at the university. Among the 1051 sampled students, only 7.4% gave the correct answer to all 7 knowledge statements about antibiotics and ABR. The main determinants of knowledge were being younger and attending to medical or life sciences majors. Almost two-thirds took an antibiotic in the previous 12 months and 24.6% reported having self-medicated with antibiotics. More than half of the sample used the Internet to seek information about antibiotics and/or ABR, and it was the strongest predictor of self-medication with antibiotics. The study findings highlighted gaps in knowledge, considerable antibiotic consumption, sometimes without prescription, together with an extensive Internet use to seek health-related information. To facilitate the health-promoting use of the Internet in conjunction with health care providers, we could make young adults aware of the rational use of antibiotics.